2003
DOI: 10.1046/j.1439-0426.2003.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding the leucine metaboliteβ-hydroxy-β-methylbutyrate (HMB) on the non-specific cellular and humoral defence mechanisms of rainbow trout (Oncorhynchus mykiss)

Abstract: Summary Previous studies have shown that leucine metabolite β‐hydroxy‐β‐methylbutyrate (HMB) increases the immune function in animals as measured by cellular and humoral immune responses. In the present study the influence of feeding HMB on the nonspecific cellular and humoral defence mechanisms and protection against furunculosis in rainbow trout (Oncorhynchus mykiss) was examined. HMB was fed in a pelleted ration at either 0 (control), 10, 25 or 50 mg  kg−1 bw day−1 for 8 weeks. Blood and pronephros cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 19 publications
(26 reference statements)
7
44
1
Order By: Relevance
“…Increases in the parameters of the innate cellular and humoral responses studied were statistically significant at all doses and for all periods that were observed. Additionally, after experimental infection, HMB in all of the doses treated reduced mortality between 20 and 50% depending on the species and the length for which the supplement was administered (Siwicki et al 2000c(Siwicki et al , 2003c. Similar effects were obtained in in vivo studies of pikeperch (Siwicki et al 2005a(Siwicki et al , 2005b(Siwicki et al , 2006a.…”
Section: Synthetic Immunostimulatorssupporting
confidence: 60%
See 1 more Smart Citation
“…Increases in the parameters of the innate cellular and humoral responses studied were statistically significant at all doses and for all periods that were observed. Additionally, after experimental infection, HMB in all of the doses treated reduced mortality between 20 and 50% depending on the species and the length for which the supplement was administered (Siwicki et al 2000c(Siwicki et al , 2003c. Similar effects were obtained in in vivo studies of pikeperch (Siwicki et al 2005a(Siwicki et al , 2005b(Siwicki et al , 2006a.…”
Section: Synthetic Immunostimulatorssupporting
confidence: 60%
“…Using vaccines and natural or synthetic preparations that have a stimulatory effect on both innate cellular and humoral defense mechanisms has limited losses caused by disease in fisheries practice. The positive effects of immunoprophylaxis are especially seen in salmonid culture and in species that are new to culture (silurids, sturgeon, pikeperch, pike, eel, tench) (Siwicki et al 1996b, 2003c, 2004c, 2005a, 2006a, 2010e, 2011d, 2015, Kolman et al 2000, Jarmo³owicz et al 2012, Kazuñ and Siwicki 2013, Kowalska et al 2015. Currently, immunoprophylaxis is divided as follows:…”
Section: Innate and Adaptive Immunoprophylaxis As A Significant Elemementioning
confidence: 99%
“…3-Hydroxy-3-methylbutyrate has been shown to be an immunomodulating compound of proliferative response of T and B lymphocytes in European catfish (Silurus glanis) at different temperatures and suggested that HMB could be used to provide the nonspecific cell-mediated immune responses suppressed by temperature in European catfish intensive culture (Siwicki et al 2004). Several previous in vitro and in vivo studies with HMB in rainbow trout and carp strongly suggest that HMB affects the macrophage and lymphocyte function, enhancing the fish resist function and ability to fight disease effectively (Siwicki et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Several feeding studies with HMB have shown that HMB may be able to help animals survive environmental stresses and disease challenges (Nissen et al 1994;Ostaszewski et al 1998;Peterson et al 1999;Siwicki et al 2004). In our preliminary in vitro study, we presented that HMB at different concentrations activated the lymphocyte proliferation in rainbow trout (Siwicki et al 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Feeding of zooplankton with carotene-synthesizing yeast was accompanied by an increase in the level of isoleucine and leucine also. As was previously shown, the derivatives of these amino acids, in particular β-hydroxyl-β-methyl-butyrate as a leucine metabolite, had the stimulating effects on the growth and immune system state of some fish species [32,33]. For example, branched-chain amino acids, namely valine, leucine and isoleucine, are important in the work of immune cells because of their important role in the synthesis of proteins, including various antibodies, immunoglobulins and acute phase proteins [34].…”
mentioning
confidence: 67%